Joint Impact Assessment of CTA's support to KENAFF (2003-2013) - Nyagah, Stellah; Gichuhi, Daniel (Technical Centre for Agricultural and Rural Cooperation, 2020)
The partnership between KENAFF and CTA was born out of the need to strengthen information flow within KENAFF, between KENAFF and its members, and between KENAFF and stakeholders, with the main goal of strengthening access to agriculture-related information by the farming community in Kenya. The partnership, which began in 2004, has impacted the Federation to a great extent, creating notable changes within the organisations’ capacities, its direct beneficiaries and the wider society.